2023
DOI: 10.3389/fonc.2023.1184841
|View full text |Cite
|
Sign up to set email alerts
|

A novel oxidative stress-related genes signature associated with clinical prognosis and immunotherapy responses in clear cell renal cell carcinoma

Abstract: BackgroundOxidative stress plays a significant role in the tumorigenesis and progression of tumors. We aimed to develop a prognostic signature using oxidative stress-related genes (ORGs) to predict clinical outcome and provide light on the immunotherapy responses of clear cell renal cell carcinoma (ccRCC).MethodsThe information of ccRCC patients were collected from the TCGA and the E-MTAB-1980 datasets. Univariate Cox regression analysis and least absolute shrinkage and selection operator (LASSO) were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…Furthermore, the biological activity of ISG15 has been found to vary across different cancer types [ 29 34 ]. Moreover, recent studies indicate that ISG15 may serve as a potential prognostic factor for adverse outcomes in individuals with ccRCC [ 35 , 36 ]. Consequently, it is crucial to investigate the precise biological role of ISG15 in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the biological activity of ISG15 has been found to vary across different cancer types [ 29 34 ]. Moreover, recent studies indicate that ISG15 may serve as a potential prognostic factor for adverse outcomes in individuals with ccRCC [ 35 , 36 ]. Consequently, it is crucial to investigate the precise biological role of ISG15 in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in ROS results in the activation of the NLRP3 inflammasome and the release of pro-inflammatory cytokines, which suppress immune surveillance, allowing tumor progression. Persistent stress increases susceptibility to cancer and enhances RCC's capacity to develop secondary manifestations through a variety of mechanisms: tumor signaling, TME reorganization, immune evasion, invasion and metastasis, DNA mutations, angiogenesis, treatment response, and induction of cellular ferroptosis/apoptosis [13,[25][26][27]. Potential inducers of cellular stress from within and outside cells are excessive amounts of oxidants [15].…”
Section: Cellular Stress In Rcc Biologymentioning
confidence: 99%
“…For instance, activating transcription factor 3 (ATF3 were correlated with RCC progression [28], genes ABCB1, AGER, E2F1, FOXM1, HADH ISG15, KCNMA1, PLG, and TEK were correlated with the clinical outcome and immune status of ccRCC patients [27], genes UCN, PLG, FOXM1, and HRH2 were associated with the ccRCC prognosis [29], long non-coding RNAs (lncRNA) SPART-AS1, AL162586.1 Based on bioinformatic analysis, several current studies have identified sets of genes related to oxidative stress (ORG). For instance, activating transcription factor 3 (ATF3) were correlated with RCC progression [28], genes ABCB1, AGER, E2F1, FOXM1, HADH, ISG15, KCNMA1, PLG, and TEK were correlated with the clinical outcome and immune status of ccRCC patients [27], genes UCN, PLG, FOXM1, and HRH2 were associated with the ccRCC prognosis [29], long non-coding RNAs (lncRNA) SPART-AS1, AL162586.1, LINC00944, LINC01550, HOXB-AS4, LINC02027, and DOCK9-DT were associated with ccRCC aggressiveness [30,31], mitochondrial genes ACAD11, ACADSB, BID, PYCR1, SLC25A27, and STAR were linked to the ccRCC prognosis [12], and genes ADAM8, CGN, EIF4EBP1, FOXM1, G6PC, HAMP, HTR2C, ITIH4, LTB4R, MMP3, PLG, PRKCG, SAA1, and VWF, and microRNAs related to the redox status and ccRCC progression [12], were found to be essential for the response to oxidative stress. Recently, a transcription factor for the oxidative stress response, broad complex-tramtrack-bric-a-brac and cap 'n' collar homology 1 (BACH1), has been labeled an essential factor involved in RCC progression in vivo [32].…”
Section: Cellular Stress In Rcc Biologymentioning
confidence: 99%
See 1 more Smart Citation